2022
DOI: 10.3390/act12010005
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments on Dielectric Barrier Discharge (DBD) Plasma Actuators for Icing Mitigation

Abstract: Ice accretion is a common issue on aircraft flying in cold climate conditions. The ice accumulation on aircraft surfaces disturbs the adjacent airflow field, increases the drag, and significantly reduces the aircraft’s aerodynamic performance. It also increases the weight of the aircraft and causes the failure of critical components in some situations, leading to premature aerodynamic stall and loss of control and lift. With this in mind, several authors have begun to study the thermal effects of plasma actuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 184 publications
1
9
0
Order By: Relevance
“…Nevertheless, these results are consistent with the values reported in the literature [28]. The observed phenomenon happens because, in fact, most of the power applied to the actuator is dissipated as dielectric and gas heating while the other part is lost as reactive power and power expended to maintain the discharge plasma [20].…”
Section: Plasma-induced Flow Mechanical Characterizationsupporting
confidence: 92%
See 1 more Smart Citation
“…Nevertheless, these results are consistent with the values reported in the literature [28]. The observed phenomenon happens because, in fact, most of the power applied to the actuator is dissipated as dielectric and gas heating while the other part is lost as reactive power and power expended to maintain the discharge plasma [20].…”
Section: Plasma-induced Flow Mechanical Characterizationsupporting
confidence: 92%
“…In addition, researchers revealed that plasma actuators produce considerable thermal effects during their operation, which can be used for icing mitigation [16][17][18][19]. Bearing this in mind, several researchers focused their studies on the operation of DBD plasma actuators for simultaneous active flow control and icing accumulation prevention [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The fixed electrode was covered with a dielectric tube, while the rotatable electrode was covered with a fabric sample . A 30 kV alternating current supply with a variac and 60 Hz cycle provided the current in mA for plasma generation . The plasma operating conditions include a 40 mA discharge current at 20 kV discharge voltage, an interelectrode gap of 3 mm, and a plasma activation time of 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Over the last decades, non-thermal plasma developed with dielectric barrier discharge (DBD) cells has been extensively studied, for various fields such as biomedical applications [1][2][3], chemical fuel reforming processes [4,5], plasma actuators for high-speed flow control [6] or icing mitigation [7] and surface modifications [8][9][10][11]. These discharges expose three different operating modes [8,[12][13][14][15]: filamentary, diffuse (or also qualified as homogeneous) and patterned (or also named as self-organized).…”
Section: Introductionmentioning
confidence: 99%